2016
DOI: 10.1189/jlb.3a0515-185r
|View full text |Cite
|
Sign up to set email alerts
|

Mincle suppresses Toll-like receptor 4 activation

Abstract: Regulation of Toll-like receptor responses is critical for limiting tissue injury and autoimmunity in both sepsis and sterile inflammation. We found that Mincle, a C-type lectin receptor, regulates proinflammatory Toll-like receptor 4 signaling. Specifically, Mincle ligation diminishes Toll-like receptor 4-mediated inflammation, whereas Mincle deletion or knockdown results in marked hyperresponsiveness to lipopolysaccharide in vitro, as well as overwhelming lipopolysaccharide-mediated inflammation in vivo. Mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…Finally, Miller and coworkers (154,155) recently demonstrated an unexpected inhibition of TLR4-dependent inflammatory cytokine expression by the CLR Dectin-1 and Mincle (Fig. 4C).…”
Section: Conflicting Signaling Of Clrs: Negative Regulationmentioning
confidence: 72%
See 1 more Smart Citation
“…Finally, Miller and coworkers (154,155) recently demonstrated an unexpected inhibition of TLR4-dependent inflammatory cytokine expression by the CLR Dectin-1 and Mincle (Fig. 4C).…”
Section: Conflicting Signaling Of Clrs: Negative Regulationmentioning
confidence: 72%
“…First, they observed that Dectin-1-deficient mice showed more hepatic fibrosis in a model of liver inflammation (154). Similarly, Mincle-deficient mice were more susceptible to endotoxic shock than were wild-type controls, resulting in higher mortality and elevated cytokine levels (155). In both studies, this enhanced susceptibility was attributed to increased levels of the TLR4 coreceptor CD14 in Dectin-1-or Mincledeficient mice.…”
Section: Conflicting Signaling Of Clrs: Negative Regulationmentioning
confidence: 97%
“…Of note, Greco et al . recently showed the downregulation of TLR4 signaling by Mincle36. Therefore, Mincle could reduce GRK2 expression in sepsis both directly and indirectly by downregulating TLR4 signaling.…”
Section: Resultsmentioning
confidence: 93%
“…MINCLE is expressed by antigen-presenting cells including macrophages, neutrophils, DCs and B cells (76). Its expression is induced by several inflammatory stimuli and stresses, such as lipopolysaccharide (LPS), tumor necrosis factor (TNF), IL-6 and saturated fatty acids (76)(77)(78)(79) and was found over-expressed in numerous inflammatory diseases (77,(80)(81)(82)(83)(84)(85)(86). Interestingly, a polymorphism in this receptor has been linked to protection against rheumatoid arthritis in humans (87).…”
Section: Clec4e (Mincle Clecsf9)mentioning
confidence: 99%
“…Alternatively, as neutrophils also express MINCLE, the use of antibodies may have exerted pleotropic effects by directly targeting or depleting neutrophils (98). Although MINCLE contributes to inflammation and immunity to contain the insult and initiate tissue repair, it can amplify collateral tissue damage and was therefore demonstrated to be implicated in numerous inflammatory diseases such as obesity, rheumatoid arthritis, allergic contact dermatitis, ischemic stroke, traumatic brain injury, hepatitis, sepsis, and multiple sclerosis (77,(80)(81)(82)(83)(84)(85)(86). Besides, MINCLE recognizes cholesterol crystals abundantly present in atherosclerotic plaques, triggering in macrophages the production of pro-inflammatory molecules (91).…”
Section: Clec4e (Mincle Clecsf9)mentioning
confidence: 99%